A theory of child adoption - Dirk Bethmann; Michael Kvasnicka (Institute for the Study of Labor (IZA), 2012)
Women can bear own children or adopt them. Extending economic theories of fertility, we provide a first theoretical treatment of the demand for adoption. We show that the propensity to adopt a child increases in the degree of own altruism, infertility, relatedness to the child, costs of own child birth, and any adoption-specific monetary return that is received net of the costs of adopting the child. Our model makes several testable predictions which receive empirical support. These include a higher propensity to adopt among infertile adults, relatives, women with high earnings potential, and celebrities.
Keywords: J12; J13; D02; 330; adoption; demand for adoption; fertility; children; altruism; Familienrecht; Nachfrage; Fruchtbarkeit; Altruismus; Theorie